Photosynthetic characteristics of cotton are enhanced by altering the timing of mulch film removal - Zhanqin ZHANG; Li ZHANG; Haiyan TIAN; Yuan NIU; Xiangkun YANG (Journal of Cotton Research, 2021)
Abstract Background The photosynthetic parameters of cotton plants may be modified by the timing of film removal during their growing period. This study was undertaken during 2015–2017 in Xinjiang, China, to determine to what extent the film mulching removal time, 1 and 10 days before the first irrigation and 1 day before the second irrigation after seedling emergence, influenced cotton’s photosynthetic characteristics. The control group (CK) was film-mulched throughout the growth stages. Results The results suggested the following: (1) Removing mulching-film within 50 days since seedling emergence had adverse effects on soil temperature and moisture. (2) Film-removal before the first or second irrigation after emergence improved the net photosynthetic rate in cotton’s later flowering stage and its transpiration rate in mid and later flowering stages while enhancing the actual electron transport rate (ETR) and maximum electron transfer rate (ETRmax) between cotton photosystems I and II. (3) Film-removal treatment also increased cotton plants’ tolerance to high irradiation after emergence, the trend was more pronounced in the early flowering stage in wetter years. (4) Leaf area index (LAI) of cotton was reduced in the film-removal treatment for which the least accumulation of dry matter occurred in a drought year (i.e., 2015). (5) Film removal caused a yield decrease in the dry year (2015), and the earlier the film was removed, the more seriously the yield decreased. Removing mulching film before the second irrigation could increase the yield of XLZ42 in the rainy year (2016) and the normal rainfall year (2017). Early film removal can increase the yield of XLZ45 in the rainy year (2016). Conclusions Collectively, our study’s experimental results indicate that applying mulch film removal at an appropriate, targeted time after seedling emergence had no adverse effects on soil moisture and temperature, and improved the photosynthetic performance of cotton, thus increased cotton yield and fiber quality, but no significant difference was reached.